How Payment Systems Affect Physicians' Provision Behaviour – An Experimental Investigation - Heike Hennig-Schmidt; Reinhard Selten; Daniel Wiesen (University of Bonn, Bonn Graduate School of Economics (BGSE), 2011)
Understanding how physicians respond to incentives from payment schemes is a central concern in health economics research. We introduce a controlled laboratory experiment to analyse the influence of incentives from fee-for-service and capitation payments on physicians' supply of medical services. In our experiment, physicians choose quantities of medical services for patients with different states of health. We find that physicians provide significantly more services under fee-for-service than under capitation. Patients are overserved under fee-forservice and underserved under capitation. However, payment incentives are not the only motivation for physicians' quantity choices, as patients' health benefits are of considerable importance as well. We find that patients in need of a high (low) level of medical services receive a larger health benefit under fee-for-service (capitation).
Keywords: C91; I11; 330; Physician payment system; laboratory experiment; incentives; fee-for-service; capitation; Ärzte; Arzthonorar; Vergütungssystem; Ökonomischer Anreiz; Gesundheitsversorgung; Test; Gesundheitsfinanzierung; Deutschland